PERBAIKAN TEKNOLOGI PENGOLAHAN, MODIFIKASI BENTUK DAN UKURAN, SERTA PENGEMBANGAN PRODUK ALTERNATIF GULA AREN - Wuri Marsigit (Universitas Bengkulu, 2018)
This project aims to provide knowledge, skills and facilitate the producers in improving the product quality and marketing through the improvement of product. This project was conducted by establishing demo plots to selected palm sugar producers. The activities include providing extension, workshops on processing, packaging technologies for palm sugar, entrepreneurship vision, business management, and strategic for marketing. This project successfully introduced the suitable technologies to produce more hygienic palm sugar with more interesting shape, more uniform in size, more long-lasting shelf-life compared to previous technologies applied by the producers. In addition, the introduction of plastic pipe made the palm sugar sap is much more sterilized and cleaner than the bamboo-based technology and furnace modification can improve processing 48 minutes faster than before and save energy up to 23 %. Although the introduced technology to process the palm sugar did not change the nutrients content, the product quality met the SNI standards. The introduced techniques also prolong the shelf life from 24 days to 126 days. There was not any difference in terms of selling prices to both products. However, the price of alternative product (powdery brown sugar) was almost 4 times higher than the traditional products (block palm sugar). Keywords: Processing, size, shape, packaging, quality, and marketing